Simulating the impact of policy changes in Mexico's PROGRESA/Oportunidades. - Azevedo, Viviane M. R.; Robles, Marcos (Journal of Development Effectiveness, 2010)
Conditional cash transfer (CCT) programmes are being widely used in developing countries to reduce poverty and enhance children's human capital. Researchers have generally relied on ex-ante evaluation models to fine-tune existing CCTs or to design new ones. One of the main pitfalls is 'targeted modelling', in which results of counterfactual simulations might be driven by model features rather than the policy objectives. This paper uses the ex-ante evaluation technique of Bourguignon et al., relaxes one of its assumptions, and simulates policy changes at the national level for the Mexican CCT. The model's result are in line with information from the national household survey, and counterfactual simulations indicate that overall school attendance can increase without additional budget.